2002
DOI: 10.3168/jds.s0022-0302(02)74400-7
|View full text |Cite
|
Sign up to set email alerts
|

A Genome Scan for Quantitative Trait Loci Affecting Milk Production in Norwegian Dairy Cattle

Abstract: An autosomal genome scan for quantitative trait loci (QTL) affecting milk production traits was carried out on the Norwegian Dairy Cattle population. Six half-sibling families with a total of 285 sons organized according to a granddaughter design were analyzed by a multiple marker regression method. Suggestive QTL for one or several of the five milk traits (milk yield, protein percentage, protein yield, fat percentage and fat yield) were detected on chromosomes 3, 5, 6, 11, 13, 18 and 20. Among these results, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 28 publications
7
62
1
Order By: Relevance
“…A consistent finding across studies reporting QTL for MY on BTA6 suggests a primary QTL segregating near the center of BTA6 close to marker BM143 [38,49,54,63] and a second QTL more distant from the centromere [54,60,68].…”
Section: Milk Yieldsupporting
confidence: 66%
See 3 more Smart Citations
“…A consistent finding across studies reporting QTL for MY on BTA6 suggests a primary QTL segregating near the center of BTA6 close to marker BM143 [38,49,54,63] and a second QTL more distant from the centromere [54,60,68].…”
Section: Milk Yieldsupporting
confidence: 66%
“…Plante et al [50] and Ron et al [55] also detected a significant QTL for FP on BTA3. QTL for FY have also been identified on this chromosome [49,53]. Many additional QTL with significant effects on FP and FY have been reported for chromosomes 5, 6, 9, 20 and 26.…”
Section: Fat Percent and Yieldmentioning
confidence: 89%
See 2 more Smart Citations
“…The same QTLs were also discovered in other populations of Holstein cattle as well as in breeds such as Finnish Ayrshire (19) and Norwegian cattle (20). Ron et al (13) showed that the region containing the analyzed QTLs was located approximately 4 cM from the BM143 microsatellite, whereas Olsen et al (20), using physical mapping, combined linkage and LD mapping and determined the location of these QTLs. They were located within a 420-kb region lying between the ABCG2 and LAP3 genes (12).…”
Section: Discussionmentioning
confidence: 99%